2009
DOI: 10.1136/gut.2009.185884
|View full text |Cite
|
Sign up to set email alerts
|

Increased colorectal cancer risk during follow-up in patients with hyperplastic polyposis syndrome: a multicentre cohort study

Abstract: Increased colorectal cancer risk during follow-up in patients with hyperplastic polyposis syndrome: a multicentre cohort study Boparai, K.S.; Mathus-Vliegen, E.M.H.; Koornstra, J.J.; Nagengast, F.M.; van Leerdam, M.; van Noesel, C.J.M.; Houben, M.; Cats, A.; van Hest, L.P.; Fockens, P.; Dekker, E. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
177
6
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(202 citation statements)
references
References 41 publications
8
177
6
11
Order By: Relevance
“…In our study, the analysis of larger lesions (28) showed that the majority were located in the proximal colon, in contrast to smaller polyps predominantly located in the rectum and the sigmoid, corroborating other publications [13,16]. One of the HPS characteristics is the simultaneous presence of different types of serrated and adenomatous polyps in the same patient [3,16,17]. However, we only found five cases of advanced lesions besides HP, which is probably due to the young age of our patients and the close follow-up with polypectomy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In our study, the analysis of larger lesions (28) showed that the majority were located in the proximal colon, in contrast to smaller polyps predominantly located in the rectum and the sigmoid, corroborating other publications [13,16]. One of the HPS characteristics is the simultaneous presence of different types of serrated and adenomatous polyps in the same patient [3,16,17]. However, we only found five cases of advanced lesions besides HP, which is probably due to the young age of our patients and the close follow-up with polypectomy.…”
Section: Discussionsupporting
confidence: 79%
“…The median number of polyps per patient varies in different studies: it was 16 in our study, which is in accordance with some authors [16,17] but is well below the average 90 polyps per patient documented by Ferrandez et al [23] Our findings are probably related to patients' age and the presence of CRC family history; in fact, Buchanan et al [20] pointed out the absence of CRC family history as an independent predictor of polyp density. Despite the predominance of small polyps, the presence of some larger lesions (high-risk lesions) is frequent.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A recent large retrospective study demonstrated that, once cleared from all polyps and under close surveillance, CRC risk in these patients is only moderately increased [3]. However, most cases of SPS remain unrecognized and as a consequence patients do not receive proper surveillance intervals, significantly increasing their risk of developing CRC [4,5]. For this reason it is important that endoscopists become acquainted with the diagnosis, risk, and optimal treatment strategies for SPS [6].…”
mentioning
confidence: 99%